HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK TK DI TK DHARMA WANITA SAKRA KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR TAHUN 2018 - Rahman, Taufikurrahman; Herlina, Herlina; Sa'di, Kholisus (Program Studi Pendidikan Luar Sekolah, 2018)
Abstrack: Based on the observations that the researchers did that the emotional social attitudes of children in Kindergarten Darma Wanita Sakra, Sakra District, East Lombok Regency have not developed optimally, among others, children have not been able to cooperate with friends, easily give up (less persistent / independent), not yet able to understand the rules and discipline , lacking a tolerant attitude towards friends. The formulation of the problem in this study was